Awakening Early Conscience: Islamic Values and Religious Moderation in Syeikh Abdurrahman Shiddiq’s Syair - Sakila, Siti Risda; Putro, Khamim Zarkasih; Hibana, Hibana (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
This article explores "Syair Ibarat dan Khabar Kiamat" by Syeikh Abdurrahman Shiddiq as a valuable resource for Islamic education and the promotion of religious moderation among young children, deeply rooted in local wisdom. Employing a qualitative-hermeneutic approach, the study reveals that the syair conveys essential Islamic values, including the shahādah (testimony of faith), ṣalāh (prayer), ṣawm (fasting), zakāh (almsgiving), and ḥajj (pilgrimage). Furthermore, it advocates for values of moderation such as tolerance, patriotism, resistance to radicalism, and cultural adaptability. The analysis draws upon various theoretical frameworks, including al-Attas's concept of ta'dīb, Gardner's theory of multiple intelligences, Gadamer's philosophical hermeneutics, Nurcholish Madjid's inclusive Islam, Lickona's character education, and the value clarification technique (VCT). The findings indicate that the syair functions not only as a piece of religious poetry but also as a culturally embedded moral resource that shapes children’s spirituality. It harmonizes Islamic teachings with cultural traditions and fosters a sense of national identity. Consequently, this syair can serve as an effective pedagogical strategy for promoting contextual and moderate Islamic character education in early childhood settings.